Improvement Performance In Designing Of 5G Communication Based Millimeter Wave Antenna - Saeed, Ali; Razzak, Audie; Hameed, Abbas (Indonesian Journal Publisher, 2025)
A critical aspect of the scientific process is the reporting Of new results in scientific journals in order to disseminate .That information to the larger community of scientists .Communication of your results contributes to the pool of Knowledge within your discipline (and others)and very Often provides information that helps others interpret .Their own experimental results .In this research paper .We discuss how to improve the performance evaluation and design in form of some review for the mathematical .Model and general shape dimensions of antenna .Consequently, high and width band wave with a good .Efficiency of transmitting .In antenna theory ,improving antenna gain is important to attain isotropic antenna ,antenna gain can be improved by the controlled behavior of frequencies ,beam forming and choosing the right antenna fabric. So that all depends on what mentioned above .hence ,the 5G networks ,antenna structuring and designing is an integral part of the communication system.